Differential Effects of Accumbens Core vs. Shell Lesions in a Rat Concurrent Conditioned Place Preference Paradigm for Cocaine vs. Social Interaction - Fritz, Michael (Public Library of Science, 2011)
BACKGROUND: A main challenge in the therapy of drug dependent individuals is to help them reactivate interest in non-drug-associated activities. Among these activities, social interaction is doubly important because treatment adherence itself depends on it. We previously developed a rat experimental model based on the conditioned place preference (CPP) paradigm in which only four 15-min episodes of social interaction with a gender- and weight-matched male conspecific (i) reversed CPP from cocaine to social interaction despite continuing cocaine training and (ii) prevented the reinstatement of cocaine CPP. In the present study, we investigated if the two subregions of the nucleus accumbens (Acb), i.e., the core (AcbC) and the shell (AcbSh), would differentially affect CPP for cocaine vs social interaction. METHODOLOGY/PRINCIPAL FINDINGS: Animals were concurrently trained for CPP pairing cocaine with one compartment and social interaction with the other (i.e., mutually exclusive stimulus presentation during training). Excitotoxic lesioning of the AcbC or the BLA shifted CPP toward social interaction, whereas AcbSh inactivation shifted CPP toward cocaine. CONCLUSIONS: Overall, our findings suggest that inactivation of the AcbC or the BLA is sufficient to shift CPP away from a drug of abuse toward social interaction. Lesioning the AcbSh produced the opposite effect.